2012
DOI: 10.1016/j.jinorgbio.2012.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Metal ions affect insulin-degrading enzyme activity

Abstract: Insulin degradation is a finely tuned process that plays a major role in controlling insulin action and most evidence supports IDE (insulin-degrading enzyme) as the primary degradative agent. However, the biomolecular mechanisms involved in the interaction between IDE and its substrates are often obscure, rendering the specific enzyme activity quite difficult to target. On the other hand, biometals, such as copper, aluminum and zinc, have an important role in pathological conditions such as Alzheimer's disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 78 publications
1
33
0
Order By: Relevance
“…[31][32][33] The further role that copper(II) might have in modulating the degradation of amylin by these enzymes has not been studied, even if this metal ion has been proven to be able to tune the enzymatic activity of some of these metalloproteases. [34][35][36] The copper(II)-driven conformational changes on h-amylin ought to have a large impact on its in vivo homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…[31][32][33] The further role that copper(II) might have in modulating the degradation of amylin by these enzymes has not been studied, even if this metal ion has been proven to be able to tune the enzymatic activity of some of these metalloproteases. [34][35][36] The copper(II)-driven conformational changes on h-amylin ought to have a large impact on its in vivo homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…MS results confirm that such different binding features affect IDE capability to degrade insulin, as the enzyme is inactive toward the hormone at acidic pH. Moreover, the insulin fragments detected by MS at basic pH involve the C-terminal residues of the insulin A chain [A (14-21) and A (15)(16)(17)(18)(19)(20)(21)] and the fragments B (17-24) and B (17)(18)(19)(20)(21)(22)(23)(24)(25). The same set of insulin fragments are known to be produced in solutions containing IDE at high concentrations, where the equilibrium in the oligomerization state of the enzyme is mainly shifted toward the dimeric and/or tetrameric forms.…”
Section: Discussionmentioning
confidence: 68%
“…Interestingly, apart from the changes on the overall activity, it is possible to note that the insulin fragments detected at alkaline pH are different from the ones detected at physiological pH. Particularly, the insulin fragments involving the C-terminal residues of the insulin B (17)(18)(19)(20)(21)(22)(23)(24)(25) are mainly produced at alkaline pH [15]. The same set of insulin fragments are known to be produced in solutions containing IDE at high concentrations [15] and therefore it is easy to speculate that the pH, as well as the enzyme concentration, has an effect on IDE oligomerization state, acidic pH shifting the equilibrium toward the monomeric form.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Catalysis with enzymes is one of the biodegradation pathways (Du et al, 2013;Pradub and Wattanachai, 2012). Research has shown that metal ions had impacts on enzyme activity and biological degradation efficiency (Jernejc and Legiša, 2002;Grasso et al, 2012;Madukasi et al, 2010;Gopinath et al, 2011). The co-occurrence of dicofol and heavy metal ions in farmland is common in China (Sun et al, 2012;Zhang and Shan, 2014).…”
Section: Introductionmentioning
confidence: 99%